The Evolution Game of Network Platform Employment Governance. (7th January 2023) - Peng, Weihua; Hou, Renyong
Abstract : Network platform employment management concerns the sustainable development effect of high-quality employment. However, new forms of employment in recent years have revealed many new employment problems, such as ineffective supervision of the laborer, the difficulty of defining the employment relationship between platform enterprises and laborers, and the chaotic evaluation and statistical standards of network platform employment. To achieve high-quality employment goals, an evolutionary game model between platform organization and platform enterprises, in which laborer supervision was considered, was theoretically constructed in this study. The evolutionary stability of each participant's strategy choice was analyzed, the influence of each factor on their strategy choice was explored, and the stability of the balancing point in the game system was further analyzed. The results of this study are as follows. (i) The laborer supervision has a significant impact on the "Compliance" behavior of platform enterprises and the "Strict-control" strategies of the platform organization. (ii) It is more conducive to strengthen laborer supervision and improve the platform enterprises' conduct code. (iii) The platform organization should give full play to the laborers' supervision utility in the design of the employment recommendation system. (iv) In order to achieve high-quality employment, mutual trust and a harmonious relationship between the platform organization and platform enterprises should be constructed. This study not only proposes an evolutionary game model of network platform employment governance but also advances policy and practical guidance for platform organizations and platform enterprises to accelerate the sustainable development of high-quality employment.